Diminished skeletal muscle microRNA expression with aging is associated with attenuated muscle plasticity and inhibition of IGF‐1 signaling. Issue 9 (13th June 2014) - Rivas, Donato A.; Lessard, Sarah J.; Rice, Nicholas P.; Lustgarten, Michael S.; So, Kawai; Goodyear, Laurie J.; Parnell, Laurence D.; Fielding, Roger A.
Abstract : Older individuals have a reduced capacity to induce muscle hypertrophy with resistance exercise (RE), which may contribute to the age‐induced loss of muscle mass and function, sarcopenia. We tested the novel hypothesis that dysregulation of microRNAs (miRNAs) may contribute to reduced muscle plasticity with aging. Skeletal muscle expression profiling of protein‐coding genes and miRNA was performed in younger (YNG) and older (OLD) men after an acute bout of RE. 21 miRNAs were altered by RE in YNG men, while no RE‐induced changes in miRNA expression were observed in OLD men. This striking absence in miRNA regulation in OLD men was associated with blunted transcription of mRNAs, with only 42 genes altered in OLD men vs. 175 in YNG men following RE, demonstrating a reduced adaptability of aging muscle to exercise. Integrated bioinformatics analysis identified miR‐126 as an important regulator of the transcriptional response to exercise and reduced lean mass in OLD men. Manipulation of miR‐126 levels in myocytes, in vitro, revealed its direct effects on the expression of regulators of skeletal muscle growth and activation of insulin growth factor 1 (IGF‐1) signaling. This work identifies a mechanistic role of miRNA in the adaptation of muscle to anabolic stimulation and reveals a significant impairment in exercise‐induced miRNA/mRNA regulation with aging.—Rivas, D. A., Lessard, S. J., Rice, N. P., Lustgarten, M. S., So, K., Goodyear, L. J., Parnell, L. D., Fielding, R. A. Diminished skeletal muscle microRNA expression with aging is associated with attenuated muscle plasticity and inhibition of IGF‐1 signaling. FASEB J. 28, 4133‐4147 (2014). www.fasebj.org